Molar and nonmolar triploidy: Recurrence or bad luck. Issue 5 (11th February 2020) - Robinson, Brianne; Brock, Jo‐Ann; Midgen, Craig; Coolen, Jillian
Abstract: In triploid pregnancies, the parental origin of the extra genome determines the phenotype and placental and fetal outcomes. Molecular genetics and placental pathology enable differentiation of molar vs nonmolar pregnancy to guide future planning. Abstract : In triploid pregnancies, the parental origin of the extra genome determines the phenotype and placental and fetal outcomes. Molecular genetics and placental pathology enable differentiation of molar vs nonmolar pregnancy to guide future planning.